Pediatric Aspects in Young Rock Climbers - Schöffl, Isabelle; Schöffl, Volker (Springer International Publishing, 2022)
As climbing consists of power and endurance aspects, it represents an ideal activity for children and adolescents. In addition to promoting the entire muscular system, it advances cognitive and mental function. However, the climbers need to be introduced to climbing stepwise according to their capabilities. Their development and individual responsibility need to be reevaluated at regular intervals. High-intensive training modalities used in elite sports should be avoided, as they can increase the risk of early arthrosis in the small finger joints as well as epiphyseal fractures. Finger pain during and after exercise must be recognized as an early warning sign.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Child development; Children; Epiphyseal fracture; Growth